2011
DOI: 10.1111/j.1651-2227.2011.02458.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between oscillometric and invasive blood pressure measurements in critically ill premature infants

Abstract: This study showed good agreement between oscillometric and invasive readings in critically ill premature infants, and further, comparable mean MAP values were found with the two methods. However, the accuracy of the oscillometric BP measurement technique fails in preterm infants with BP within the lower limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 18 publications
3
44
2
1
Order By: Relevance
“…In practice, the cuff should cover about 2/3rds of the upper arm. Although there may be inaccuracies between oscillometric noninvasive blood pressure measurements compared with invasive arterial blood pressure measurements, the preponderance of studies suggests that in preterm infants during hypotension, there is either good agreement or an overestimation of the blood pressure using oscillometric methods (39)(40)(41)(42)(43)(44). Studies in term infants also find a bias in this direction (45)(46)(47).…”
Section: Inaccuracy Of Blood Pressure Measurementmentioning
confidence: 99%
“…In practice, the cuff should cover about 2/3rds of the upper arm. Although there may be inaccuracies between oscillometric noninvasive blood pressure measurements compared with invasive arterial blood pressure measurements, the preponderance of studies suggests that in preterm infants during hypotension, there is either good agreement or an overestimation of the blood pressure using oscillometric methods (39)(40)(41)(42)(43)(44). Studies in term infants also find a bias in this direction (45)(46)(47).…”
Section: Inaccuracy Of Blood Pressure Measurementmentioning
confidence: 99%
“…However, invasive arterial BP (IABP) measurement is considered as a standard of monitoring in patients requiring a more intense BP control and monitoring. [1234] The two monitoring techniques often produce different values; however, the relationship between these two techniques has been poorly studied. A recent study by Wax et al .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies that have reported a good correlation between intra-arterial and oscillometric readings have not conducted an appropriate evaluation for the agreement between the two methods, thus incorrectly attributing correlation as being equivalent to comparability or agreement [32][33][34][35][36]. Other studies in which agreement between the two methods of BP measurement have been evaluated have 'overlooked' the wide ranges of the data, once again incorrectly concluding that these two methods provide similar BP measurements [30,[37][38][39].…”
Section: Challenges With Blood Pressure Measurementsmentioning
confidence: 84%